Manufacture Glycerol Byproducts From Waste Cooking Oil Through The Transesterification Process In Various Brands Of Oil In The Indonesian Market - suryani, monica (International Journal of Science, Technology & Management, 2021)
Abstract. Waste cooking oil is oil that has been used repeatedly, up to 2-4 times in the frying pan. The large number of Indonesian people who often consume waste cooking oil due to economic factors. The use of oil repeatedly reduces the nutritional value and affects the quality and value of fried food ingredients. However, this waste is very useful, it can be processed into glycerol which is useful in the cosmetic industry. The objective of this research is to prove that the glycerol byproduct of waste cooking oil with various oil brands in the Indonesian market has similar functional groups to commercial glycerol. The research was carried out experimentally by making glycerol using waste cooking oil. Glycerol is made using a transesterification process. Transesterification (alcoholic reaction) is a vegetable fat or oil that is reacted with alcohol to produce an ester and glycerol as a byproduct with the help of an alkaline catalyst. Evaluation of glycerol includes organoleptic, specific gravity, viscosity, glycerol content, ash content, moisture content, and sugar content. The results of the study using FTIR showed that the commercial glycerol wave number was 3291cm-1, brand X at 3291cm-1, and brand Y at 3267cm-1, which indicated the presence of an OH (hydroxyl) group. Commercial glycerol absorption bands at 2931 and 2877 cm-1, brand X at 2933 and 2879 cm-1, and brand Y at 2931 and 2877cm-1, indicating the presence of aliphatic (alkyl) CH groups. Based on the research results, it can be concluded that the glycerol byproduct of waste cooking oil using the Indonesian market brands X and Y has similar functional groups to commercial glycerol. However, glycerol is the byproduct of waste cooking oil brand X which has the most similarities with commercial glycerol. Keyword: waste cooking oil, glycerol, transesterification, oil Indonesian market